2021
DOI: 10.1021/acsomega.1c04105
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Radio Frequency Plasma Power on the Structure, Crystallinity, Dislocation Density, and the Energy Band Gap of ZnO Nanostructure

Abstract: The aim of this study is to investigate the effect of radio frequency (RF) plasma power on the morphology, crystal structure, elemental chemical composition, and optical properties of ZnO nanostructure using a direct current magnetron sputtering technique. This study emphasized that the growth rate and surface morphology of the polycrystalline ZnO were enhanced as the radio frequency (RF) plasma power increased. This can be observed by fixing other parameters such as the growth time, substrate temperature, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…11,13 Due to its nontoxic nature, high chemical and mechanical stability, excellent electrical properties, and relatively economical fabrication cost, ZnO emerges as a promising candidate for the development of cost-effective photodetectors across a diverse range of applications, including wearable and personal-ized UV monitoring devices. 9 Several nanofabrication methods, such as radio frequency magnetron sputtering (RFMS), 14 flame spray pyrolysis (FSP), 11,15,16 chemical vapor deposition (CVD), 17,18 pulsed laser deposition (PLD), 19 hydrothermal (HT), 20,21 and conventional spin coating based on sol−gel system 12,22,23 have been used, demonstrating significant improvement over bulk equivalents. 11 In our previous work, 11,13,24,25 we reported the flame-made ultraporous nanoparticle networks (UNN) as highly performing nanostructures for visible-blind UV photodetectors, demonstrating high photocurrents (hundreds of μA) and low nanoampere dark current under low UVR density of 100 μW• cm −2 and an applied bias of a few volts (1−5 V).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13 Due to its nontoxic nature, high chemical and mechanical stability, excellent electrical properties, and relatively economical fabrication cost, ZnO emerges as a promising candidate for the development of cost-effective photodetectors across a diverse range of applications, including wearable and personal-ized UV monitoring devices. 9 Several nanofabrication methods, such as radio frequency magnetron sputtering (RFMS), 14 flame spray pyrolysis (FSP), 11,15,16 chemical vapor deposition (CVD), 17,18 pulsed laser deposition (PLD), 19 hydrothermal (HT), 20,21 and conventional spin coating based on sol−gel system 12,22,23 have been used, demonstrating significant improvement over bulk equivalents. 11 In our previous work, 11,13,24,25 we reported the flame-made ultraporous nanoparticle networks (UNN) as highly performing nanostructures for visible-blind UV photodetectors, demonstrating high photocurrents (hundreds of μA) and low nanoampere dark current under low UVR density of 100 μW• cm −2 and an applied bias of a few volts (1−5 V).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The direct bandgap structure of ZnO enables a sharp photoresponse contrast between the visible and UV spectra, , facilitating efficient detection of UV light and a high selectivity against the visible spectrum ( R UV / R vis ). , Due to its nontoxic nature, high chemical and mechanical stability, excellent electrical properties, and relatively economical fabrication cost, ZnO emerges as a promising candidate for the development of cost-effective photodetectors across a diverse range of applications, including wearable and personalized UV monitoring devices . Several nanofabrication methods, such as radio frequency magnetron sputtering (RFMS), flame spray pyrolysis (FSP), ,, chemical vapor deposition (CVD), , pulsed laser deposition (PLD), hydrothermal (HT), , and conventional spin coating based on sol–gel system ,, have been used, demonstrating significant improvement over bulk equivalents …”
Section: Introductionmentioning
confidence: 99%
“…Dislocation density d ( ) is an indicator of defects in the lattice and it may favour the aggregation of native defects in the ZnO lattice [37]. Abdul Rahman et al observed that non-stochiometry in ZnO lattice increases dislocation density [38]. It is also observed that the formation energy for the point defects is reduced due to dislocations in the lattice [39].…”
Section: Xrd and Raman Spectramentioning
confidence: 99%
“…19 Similarly, ZnO NPs have evolved into a very valuable material over time due to their eco-friendly attributes, great stability, low cost, and simple manufacturing methods. 20 Meanwhile, ZnO/CuO NCs serve as a prominent example owing to their antimicrobial activities. 21 It was discovered that Cu-doped ZnO nanorods have higher photocatalytic and antibacterial properties than pure nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…CuO NPs have strong electron correlation effects, high heat conductivity, and spin dynamics . Similarly, ZnO NPs have evolved into a very valuable material over time due to their eco-friendly attributes, great stability, low cost, and simple manufacturing methods . Meanwhile, ZnO/CuO NCs serve as a prominent example owing to their antimicrobial activities .…”
Section: Introductionmentioning
confidence: 99%